2015
DOI: 10.1007/s12541-015-0231-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mode variable stiffness actuator using two-stage worm gear transmission for safe robotic manipulators

Abstract: In this paper, we propose a new type of active variable stiffness actuator (VSA) by using a unique differential worm gear mechanism where a set of compressible coil springs are installed. The stiffness of the VSA is varied depending on the compressed amount of the coil springs; large compression results in an effectively stiff joint, and vice versa (compliant mode). Interestingly, an ideal rigid joint is also realizable if the springs' reactive force is made larger than the external load (rigid mode). The VSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The second actuator adjusts the stiffness by changing the transmission-ratio or transmission-angle, controlling the pre-stress on a nonlinear spring or the physical stiffness properties [19,20]; as advantage, the output torque is not influenced. Jeong et al [21] reported on the use of two-worm gear transmission to compress two coiled springs and change their output stiffness. In continuum robotics with wire transmission, increasing tension in the wires is used to increase stiffness [11,22].…”
Section: Variable Stiffness and Impedance Actuatorsmentioning
confidence: 99%
“…The second actuator adjusts the stiffness by changing the transmission-ratio or transmission-angle, controlling the pre-stress on a nonlinear spring or the physical stiffness properties [19,20]; as advantage, the output torque is not influenced. Jeong et al [21] reported on the use of two-worm gear transmission to compress two coiled springs and change their output stiffness. In continuum robotics with wire transmission, increasing tension in the wires is used to increase stiffness [11,22].…”
Section: Variable Stiffness and Impedance Actuatorsmentioning
confidence: 99%
“…9 Another potential benefit of a worm-wheel gear is its unique property of self-locking or non-backdrivability that allows it to be driven on the side of input and not back driven on the load side. [10][11][12][13][14] Therefore, actuators do not need to stay powered all the time to hold or lift the loads in a particular position. These promising features make the worm-wheel gear transmission a desirable candidate for several robotic applications, including rescue operations.…”
Section: Introductionmentioning
confidence: 99%
“…That makes robots safe and improves their adaptability in the human-robot cooperation field [1]. In literature, many applications of the variable stiffness system (VSS) [2] such as shock absorbance [3][4][5], stiffness variability with a constant load [6,7], and cyclic movement [8], the safety robot [9] proved the effectiveness of the variable stiffness system although this research focused on tuning the system stiffness optimally. Normally, primary torque or force of these VSSs is generated by electric motors [3][4][5]8,9], or pneumatic actuators [6,7,9].…”
Section: Introductionmentioning
confidence: 99%